Malignant mesothelioma diagnosed at a younger age is associated with heavier asbestos exposure. (30th June 2018) - Dragani, Tommaso A; Colombo, Francesca; Pavlisko, Elizabeth N; Roggli, Victor L
Abstract : In malignant mesothelioma patients, we found that diagnosis occurred at a younger age in subjects with high levels of asbestos bodies and fibers in lung tissue, suggesting that asbestos is also involved in the tumor progression of the disease. Abstract: Asbestos exposure is the main etiology of malignant mesothelioma, but there are conflicting data on whether the intensity of exposure modulates the development of this disease. This study considered 594 patients with malignant mesothelioma for whom count data on asbestos bodies and fibers (per gram of wet lung tissue) were available. The relationships between age at diagnosis (a time-to-event outcome variable) and these two measures of internal asbestos exposure, along with other possible modulating factors (sex, tumor location, histological subtype and childhood exposure), were assessed on multivariable Cox proportional hazard models, stratifying by decade of birth year. For both measures of asbestos in lung tissue, younger age at diagnosis was associated with higher internal measures of exposure to asbestos. Stratified Cox analyses showed that for each doubling in asbestos body count patients were 1.07 times more likely to be diagnosed at a younger age [hazard ratio (HR) = 1.07; 95% confidence interval (CI), 1.04–1.09; P = 2.2 × 10 −7 ] and for each doubling in asbestos fiber count patients were 1.13 times more likely to be diagnosed at a younger age (HR = 1.13; 95% CI, 1.09–1.17; P = 8.6 × 10 −11 ). None of the other variables considered were associated with age at diagnosis. Our finding that tumors become clinically apparent at a younger age in heavily exposed subjects suggests that asbestos is involved not only in the malignant mesothelioma tumor initiation but, somehow, also in the progression of the disease.